Duplications of the neuropeptide receptor gene VIPR2 confer significant risk for schizophrenia. - MORRIS, DEREK; CORVIN, AIDEN; GILL, MICHAEL (My University, 2011)
Rare copy number variants (CNVs) play a prominent role in the etiology of schizophrenia and other neuropsychiatric disorders 1 . Substantial risk for schizophrenia is conferred by large (>500 kb) CNVs at several loci, including microdeletions at 1q21.1 2 , 3q29 3 , 15q13.3 2 and 22q11.2 4 and microduplication at 16p11.2 5 . However, these CNVs collectively account for a small fraction (2-4%) of cases, and the relevant genes and neurobiological mechanisms are not well understood. Here we performed a large two-stage genome-wide scan of rare CNVs and report the significant association of copy number gains at chromosome 7q36.3 with schizophrenia (P= 4.0?10 -5 , OR = 16.14 [3.06, ? ]). Microduplications with variable breakpoints occurred within a 362 kb region and were detected in 29 of 8,290 (0.35%) patients versus two of 7,431 (0.03%) controls in the combined sample (p-value= 5.7?10-7, odds ratio (OR) = 14.1 [3.5, 123.9]). All duplications overlapped or were located within 89 kb upstream of the vasoactive intestinal peptide receptor VIPR2. VIPR2 transcription and cyclic-AMP signaling were significantly increased in cultured lymphocytes from patients with microduplications of 7q36.3. These findings implicate altered VIP signaling in the pathogenesis of schizophrenia and suggest VIPR2 as a potential target for the development of novel antipsychotic drugs
PUBLISHED
PMID:21346763
Keywords: pathogenesis of schizophrenia; pathogenesis of schizophrenia; Genes & Society; Neuroscience